ASPECTS REGARDING MUSCULOSKELETAL PAIN IN PEDIATRIC PATIENTS WITH MALIGNANCY - Cristina Oana Marginean; Maria Despina Baghiu; Adienne Horvath; Alina Grama; Andreea Durlan (Amaltea Medical Publishing House, 2017)
Introduction. Musculoskeletal pain is among the most common complaints of children and most episodes are self-limiting. However, in some cases, it is the first sign of malignancy. Objectives. Evaluation of the frequency and characteristics of musculoskeletal complaints as initial symptoms present in children with newly diagnosed cancer. Material and methods. Retrospective study that included 231 children with various malignancies diagnosed in the Pediatric Clinic I, Targu Mures, during 2000-2015. The collected data were: age at diagnosis, clinical features, laboratory findings and final diagnoses. Results. 23% of children with cancer had musculoskeletal symptoms at initial presentation. The average time between the onset and final diagnosis was 60 days. The most common complaints were arthralgia (50%) involving large joints. Juvenile rheumatoid arthritis has been the most common initial diagnosis in 7 of 54 patients (13%). Anemia was the most frequent hematological initial finding. All patients had elevated erythrocyte sedimentation rate (ESR) and lactate dehydrogenase (LDH). Malignancies diagnosed were: acute lymphoblastic leukemia and myeloid leukemia, lymphomas and solid tumors. Conclusions. Early diagnosis of cancer and adequate treatment are essential to improving the prognosis and can be done including cancer in the differential diagnosis of rheumatic diseases in children who initially accuse musculoskeletal pain.